Emotional Processing and Metacognitive Awareness for Persecutory Delusions - Hepworth, C; Startup, H; Freeman, D (John Wiley and Sons, 2013)
One potential target for intervention for individuals with persecutory delusions is direct enhancement of emotional processing. The clinical intervention literature describes a range of techniques that have been used to enhance emotional processing. Examination of the focus of these interventions, and study of the theoretical literature, identified three key mechanisms that might impede emotional processing: (1) emotional inhibition; (2) a lack of metacognitive awareness; and (3) nonacceptance (avoidance) of internal experiences. This chapter describes the authors' recent work examining this. A brief intervention, emotional processing and metacognitive awareness (EPMA), was developed and piloted with patients who had persistent persecutory delusions. It was found that an intervention that directly targeted worry reduced levels of persecutory delusions and associated distress. The results indicate that encouraging patients to talk about their delusional experiences in a structured intervention such as EPMA may have therapeutic benefits. © 2013 John Wiley and Sons, Ltd.